2018
DOI: 10.1002/cphc.201800225
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Electric Field on the Spectroscopic Properties of the Isolated Green Fluorescent Protein Chromophore Anion

Abstract: Here we uncover the direct effect of a high electric field on the absorption by the Green Fluorescent Protein chromophore anion isolated in vacuo based on gas-phase action spectroscopy. Betaine is a strong molecular dipole that creates an electric field of ∼70 MV/cm when attached to the ion at the phenolate oxygen, more than half the actual field from the protein matrix and pointing in the same direction. Nevertheless, the shift in absorption is limited (0.08 eV), supporting earlier conclusions, but subject to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The absorption by the 2 + B complex has a maxiumum at 460 nm, and is shifted by approximately 0.6 eV as compared with the bare chromophore. This is an anomalously large blue shift, being a factor of two larger than the largest blue shift due to betaine complexation measured so far [27,28]. The absorption band of the 1 + B complex is considerably wider and peaked at 410 nm.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The absorption by the 2 + B complex has a maxiumum at 460 nm, and is shifted by approximately 0.6 eV as compared with the bare chromophore. This is an anomalously large blue shift, being a factor of two larger than the largest blue shift due to betaine complexation measured so far [27,28]. The absorption band of the 1 + B complex is considerably wider and peaked at 410 nm.…”
Section: Resultsmentioning
confidence: 59%
“…more than six times larger than that of water. It has recently been shown that electrospraying a solution containing the chromophore of choice and betaine results in the production of mixed complexes [27,28]. The structure of these complexes is expected to be one where the negative part of the betaine is located close to the positive charge in the chromophore, inducing a strong local electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Most experiments are done at room temperature but it is worth to mention two unique setups built by Kappes, Schooss and their co-workers [252] and Ferzoco and co-workers [253] where ions are cooled to low temperatures. The former operates close to 77 K (liquid nitrogen temperature) while in the latter, ions are stored in a LQT at ambient to cryogenic temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the intrinsic properties, the molecule has to be studied isolated in the gas phase. After the absorption spectrum of the bare Chl is established, perturbations can be included by complexation of the pigment with various adducts to study the effect of individual interactions …”
Section: Figurementioning
confidence: 99%
“…After the absorption spectrum of the bare Chl is established, perturbations can be included by complexation of the pigment with various adducts to study the effect of individual interactions. [8][9][10] The first gas-phase absorption measurementso fC hl revealed as ignificant blueshift of the Qa sw ella st he Soret bands compared to Chl-containingproteins, which emphasized the strong effect of the microenvironment on the overall transition energies. [11][12][13] The binding of an egatively charged axial ligand to the Mg 2 + center [14] as well as excitonic coupling between two Chl molecules [15] produce large colors hifts and can to some extent account for the strong spectral variation between bare Chls and pigment-proteins.…”
mentioning
confidence: 99%